2016
DOI: 10.4236/jbbs.2016.612044
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Condition-Related Changes in the Prefrontal Cortex Activity during Rest

Abstract: The prefrontal cortex (PFC) plays an important role in cognitive process related to executive function, but is also active during resting states. Quantifying prefrontal cortex activity during resting states provides a baseline for interpreting task-induced brain activity. Researchers commonly use resting conditions where participants are prompted to stare at a screen (eyes open) or close their eyes (eyes closed). Are these two conditions equivalent representations of a baseline resting state? Further, does pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Therefore, in this study we measured connectivity between frontal, temporal, and parietal brain areas, which we will refer to as fronto-temporoparietal connectivity, as a proxy for the DMN. The approach of studying portions of the DMN as a proxy for this network has been recently adopted by adult studies, focusing in particular on the mPFC (Durantin, Dehais, & Delorme, 2015;Liang, Chen, Shewokis, & Getchell, 2016;Sasai et al, 2012) and the parietal lobes (Rosenbaum et al, 2017;Sasai et al, 2012).…”
mentioning
confidence: 99%
“…Therefore, in this study we measured connectivity between frontal, temporal, and parietal brain areas, which we will refer to as fronto-temporoparietal connectivity, as a proxy for the DMN. The approach of studying portions of the DMN as a proxy for this network has been recently adopted by adult studies, focusing in particular on the mPFC (Durantin, Dehais, & Delorme, 2015;Liang, Chen, Shewokis, & Getchell, 2016;Sasai et al, 2012) and the parietal lobes (Rosenbaum et al, 2017;Sasai et al, 2012).…”
mentioning
confidence: 99%
“…Data were subsequently converted to changes in concentration using the modified Beer-Lambert law (Cope and Delpy, 1988) and depicted into four outcome measures: change in oxygenated hemoglobin (ΔHbO), change in deoxygenated hemoglobin (ΔHbR), total change in hemoglobin (ΔHbT) and total change in oxygenation (ΔOxy). We restricted our analysis to ΔHbO because our preliminary analysis showed high correlation among ΔHbO, ΔHbT, and ΔOxy, in addition to ΔHbO having stronger and more wide-spread signals than those from ΔHbR and ΔHbT (Zhang et al, 2011), including in the ToH task (Liang et al, 2016a,b). Furthermore, it has been shown that ΔHbO has a strong correlation to BOLD signal whereas ΔHbR has a weak correlation (Strangman et al, 2002), in addition to better signal-to-noise ratio (SNR) than ΔHbR (Hoshi, 2007; Zhang et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the ToH puzzle has the advantage of being sensitive to disruption in the PFC (Simon, 1975; Saint-Cyr et al, 1988; Casey et al, 1994; Goel and Grafman, 1995). Additionally, the activity of the PFC during the computerized version of ToH has been shown using different neuroimaging techniques such as fMRI (Head et al, 2002; Griebling et al, 2010; Crescentini et al, 2012) and EEG (Ruiz-Díaz et al, 2012; Guevara et al, 2013), in addition to functional near-infrared spectroscopy (fNIRS; Liang et al, 2016a,b). fNIRS is a neuroimaging tool that is non-invasive, portable, affordable, and safe for continuous and repeated measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The team also brings experience in the development and implementation of tailored technology‐based health promotion interventions; community‐engaged mixed‐methods research; and embodied interactive games. The development work expanded upon team members' prior work with health game development (Ruggiero et al, 2020; Ruggiero et al, 2023), research in senior centers using commercial exergames (Orsega‐Smith et al, 2012; Orsega‐Smith et al, 2020), use of fNIRS in adults participating in cognitively stimulating computer‐based tasks (Bakhshipour et al, 2020; Koiler et al, 2022; Liang et al, 2016; Milla et al, 2019), and designing embodied interactive systems and games using Microsoft Kinect for healthcare education and rehabilitation (Barmaki & Hughes, 2018a; Barmaki & Hughes, 2018b; Barmaki et al, 2019; Bork et al, 2017; Yu et al, 2018).…”
Section: Multidisciplinary Development and Research Teammentioning
confidence: 99%